Dynamic contrast‐enhanced MRI: Study of inter‐software accuracy and reproducibility using simulated and clinical data. Issue 6 (21st December 2015) - Beuzit, Luc; Eliat, Pierre‐Antoine; Brun, Vanessa; Ferré, Jean‐Christophe; Gandon, Yves; Bannier, Elise; Saint‐Jalmes, Hervé
Abstract : Purpose: To test the reproducibility and accuracy of pharmacokinetic parameter measurements on five analysis software packages (SPs) for dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI), using simulated and clinical data. Materials and Methods: This retrospective study was Institutional Review Board‐approved. Simulated tissues consisted of pixel clusters of calculated dynamic signal changes for combinations of Tofts model pharmacokinetic parameters (volume transfer constant [ K trans ], extravascular extracellular volume fraction [ v e ]), longitudinal relaxation time ( T 1 ). The clinical group comprised 27 patients treated for rectal cancer, with 36 3T DCE‐MR scans performed between November 2012 and February 2014, including dual‐flip‐angle T 1 mapping and a dynamic postcontrast T 1 ‐weighted, 3D spoiled gradient‐echo sequence. The clinical and simulated images were postprocessed with five SPs to measure K trans, v e, and the initial area under the gadolinium curve (iAUGC). Modified Bland–Altman analysis was conducted, intraclass correlation coefficients (ICCs) and within‐subject coefficients of variation were calculated. Results: Thirty‐one examinations from 23 patients were of sufficient technical quality and postprocessed. Measurement errors were observed on the simulated data for all the pharmacokinetic parameters and SPs, with a bias ranging from −0.19 min −1 to 0.09 min −1 for K trans, −0.15 to 0.01 for v e, and −0.65 to 1.66 mmol.L −1 .min for iAUGC. The ICC between SPs revealed moderate agreement for the simulated data ( K trans : 0.50; v e : 0.67; iAUGC: 0.77) and very poor agreement for the clinical data ( K trans : 0.10; v e : 0.16; iAUGC: 0.21). Conclusion: Significant errors were found in the calculated DCE‐MRI pharmacokinetic parameters for the perfusion analysis SPs, resulting in poor inter‐software reproducibility. J. Magn. Reson. Imaging 2016;43:1288–1300.